2017
DOI: 10.1016/j.cropro.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of brown rot in stone fruit using Bacillus amyloliquefaciens CPA-8 under field conditions

Abstract: Different treatments based on the biocontrol agent (BCA) Bacillus amyloliquefaciens CPA-8 to control brown rot under field conditions were evaluated as alternative to chemical applications. As part of a well-designed disease program that enables the integration of BCAs into cropping systems, testing of the sensitivity of Monilinia laxa and Monilinia fructicola at different doses of CPA-8 were conducted in stone fruit. CPA-8 dose of 10 7 CFU mL-1 reduced more than 60.0 and 75.5 % of brown rot incidence and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…The efficacy of preharvest and postharvest applications of the BCA B. amyloliquefaciens CPA‐8 to control brown rot in stone fruit has already been demonstrated . However, to ensure its efficacy after field treatment, it is necessary to know the ecological fitness of this bacterium, which is determined by the physical and microbiological environment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of preharvest and postharvest applications of the BCA B. amyloliquefaciens CPA‐8 to control brown rot in stone fruit has already been demonstrated . However, to ensure its efficacy after field treatment, it is necessary to know the ecological fitness of this bacterium, which is determined by the physical and microbiological environment .…”
Section: Discussionmentioning
confidence: 99%
“…alone or in combination with other postharvest treatments . Moreover, recent studies revealed that applications of B. amyloliquefaciens during the preharvest of peaches and nectarines substantially reduced brown rot decay during postharvest …”
Section: Introductionmentioning
confidence: 99%
“…Numerous microbial antagonists of postharvest phytopathogens have been identified in laboratory and field studies and exploited commercially [12]. To date, the development of products based on beneficial microorganisms is relevant to reducing chemical contaminants in the food supply [80].…”
Section: Commercializing Biological Productsmentioning
confidence: 99%
“…In other hand, control efficacy achieved by a combination of BCAs exhibiting different mechanisms of biocontrol may also result in antagonistic, additive or synergistic effects (Guetsky et al, 2002(Guetsky et al, , 2001. Bacillus amyloliquefaciens CPA-8 has been reported as an effective antagonist against preharvest (Gotor-Vila et al, 2017a), and postharvest brown rot caused by Monilinia spp. based mainly on its capability of production of powerful antifungal metabolites such us fengycinlike lipopeptides and other mechanisms of action such as competition and production of volatiles The combination of different mechanisms of action, competition by Pf909 and antibiosis or volatiles by CPA8, could improve brown rot biocontrol obtained by each one.…”
Section: Penicillium Frequentansmentioning
confidence: 99%